Morphine affects brain activity and volumes in preterms: An observational multi-center study. (May 2020) - Tataranno, M.L.; Gui, L.; Hellström-Westas, L.; Toet, M.; Groenendaal, F.; Claessens, N.H.P.; Schuurmans, J.; Fellman, V.; Sävman, K.; de Vries, L.S.; Huppi, P.; Benders, M.J.N.L.
Abstract: Objective: We hypothesized that morphine has a depressing effect on early brain activity, assessed using quantitative aEEG/EEG parameter and depressed activity will be associated with brain volumes at term in extremely preterm infants. Study design: 174 preterm infants were enrolled in 3 European tertiary NICUs (mean GA:26 ± 1wks) and monitored during the first 72 h after birth with continuous 2 channel aEEG. Six epochs of aEEG recordings were selected and minimum amplitude of aEEG (min aEEG), percentage of time amplitude <5 μV (% of time < 5 μV), spontaneous activity transients (SATrate) and interSAT interval (ISI) were calculated. For infants receiving morphine, the cumulative morphine dosage was calculated. In a subgroup of 58 infants, good quality MRI at term equivalent age (TEA) and the cumulative morphine dose until TEA were available. The effects of morphine administration and cumulative dose on aEEG/EEG measures and on brain volumes were investigated. Results: Morphine administration had a significant effect on all quantitative aEEG/EEG measures, causing depression of early brain activity [longer ISI (β 2.900), reduced SAT rate (β −1.386), decreased min aEEG (β −0.782), and increased % of time < 5 μV (β 14.802)] in all epochs. A significant effect of GA and postnatal age on aEEG/EEG measures was observed. Cumulative morphine dose until TEA had a significant negative effect on total brain volume (TBV) (β −8.066) and cerebellar volume (β −1.080). Conclusions: Administration of sedative drugs should be considered when interpreting aEEG/EEG together with the negative dose dependent morphine impact on brain development. Highlights: Our findings suggest that morphine strongly reduces brain activity, with a dose dependent effect. The administration of sedative drugs should be considered when interpreting aEEG. preterm infant cerebral activity increases with increasing maturity and is influenced by postnatal age. Cumulative morphine dose has a negative effect on total brain volume, deep grey matter and cerebellar volume.